(untitled) - Cheney, E. W (Belmont, CA, 2008)
The book provides a survey of numerical mathematics. Presents a wide variety of topics, including some advanced concepts that play an important role in current scientific computing
Keywords: Numerical analysis,Giải tích số học; Data processing,Xử lý dữ liệu